Nanoalloys Composed of Platinum Group Metals and p‐Block Elements for Innovative Catalysis - Megumi Mukoyoshi; Hiroshi Kitagawa (Advanced Energy & Sustainability Research)
Alloy nanoparticles based on platinum group metals (PGMs) have been intensively investigated in various fields, especially in catalysis. Recently, the scope of alloying has expanded to include not only d‐block transition metals but also p‐block elements, which have a wide range of properties that are very different from those of d‐block transition metals. By alloying PGMs with p‐block elements, the electronic structure and surface properties of the catalysts can be tuned, enhancing their catalytic performance. The focus of this review is on PGM–p‐block element nanoalloys, their synthesis methods, characterization techniques, and catalytic properties. In addition to typical binary crystalline alloys, such as solid‐solution and intermetallic alloys, this review also highlights the potential of multielement, amorphous, or liquid alloys, which have recently garnered much attention. The review aims to provide valuable perspectives for the development of PGM‐based sustainable and innovative catalysis, while also addressing the current challenges and future directions in this field.